Globe Telecom and Smart Communication a comparative analysis of marketing strategies - Maayo, Beth.; Medalla, Ivee T.; Ochon, Janice Ava D.; Pescadera, Elbert E.; Ponsaran, Karen E. (2002)
This descriptive research aimed at determining the comparison of the marketing strategies being applied by GLOBE Telecom and SMART Communications. specifically, the study sought answers to the following questions : What are the common marketing strategies being applied by GLOBE Telecommunication and SMART Communication companies that enable them to dominate the local market? This study utilized the descriptive method of research. The respondents included 30 persons who were all students. A questionnaire-checklist was utilized in order to gather data needed for the study. The data were subjected to frequency count rating to determine any differences in the marketing strategies used by GLOBE Telecommunication and SMART Communications. Based on the findings, the following conclusions were drawn: 1. GLOBE TELECOM emerged as the key player in the field of mobile communications. Survey shows that they have the most effective marketing strategies ince majority of the respondents were in favor of the services offered and the features they provide. ; 2. Both mobile companies continue to improve their services and features in order to provide consumers wide variety of choices in terms of services and features. In the light of the aforementioned conclusions, the following recommendations were advanced : 1. Both mobile companies should improve the services that are offered, allow more innovation in terms of technology to suit the variety of needs and lifestyles. They should also provide quality service to their patrons. ; 2. Widen the coverage of their marketing areas as well as network coverage ; 3. Give more emphasis to the market, especially to their target market/area. Improve advertising programs to enable to reach its target market.
Management Research. -- [Iloilo City] : UPV-[CM], March 22, 2002.